Empowerment Series: Foundations of Social Policy: Social Justice in Human Perspective, 6th Edition - Amanda S. Barusch (Cengage Learning, 2017)
Reflecting the idea that social justice is a primary mission of the social work profession, this text provides a thorough grounding in policy analysis -- with coverage of policy practice and a unique emphasis on the human dilemmas inherent in the pursuit of social justice. Aligned with current standards and core competencies, FOUNDATIONS OF SOCIAL POLICY, 6th Edition introduces you to philosophical perspectives on what constitutes social justice, and identifies values and assumptions reflected in contemporary policy debates. Students have said they like how this book deepens their understanding of current developments, including topics straight from the headlines. The book also introduces you to people whose lives are influenced by U.S. policies, as well as to those who have shaped the policies.